2003
DOI: 10.2169/internalmedicine.42.730
|View full text |Cite
|
Sign up to set email alerts
|

Thrombopoietin-Producing Hepatocellular Carcinoma

Abstract: gesting TPO-producing HCC. (Internal Medicine 42: 730-734, 2003)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…8,17,18 The reasons are unclear but one possibility is production of a thrombopoietic factor by HCC cells. 19 These observations require further study.…”
Section: Discussionmentioning
confidence: 97%
“…8,17,18 The reasons are unclear but one possibility is production of a thrombopoietic factor by HCC cells. 19 These observations require further study.…”
Section: Discussionmentioning
confidence: 97%
“…Patients with HCVrelated HCC had a higher prevalence of thrombocytopenia than patients with HBV-related HCC (63% vs. 42%). Although a patient with thrombopoietin-produ- cing HCC has been reported, 34 the significance of this finding is limited. The results from Pilot Study 3 indicated that the prevalence of thrombocytopenia was slightly greater in patients with chronic HCV infection than in patients with chronic HBV infection (26.7% vs. 5.6%).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the well-described paraneoplastic syndrome of thrombocytosis which occurs in 2.7% of HCCs. It is caused by tumors that secrete excessive amounts of thrombopoietin and is associated with larger tumor size and worse survival [32,33]. It is unclear why the survival advantage in patients with a platelet count below 100,000 per mm 3 is not seen in HIVinfected patients.…”
Section: Discussionmentioning
confidence: 99%